2012
DOI: 10.1098/rspb.2012.0869
|View full text |Cite
|
Sign up to set email alerts
|

Dolphin genome provides evidence for adaptive evolution of nervous system genes and a molecular rate slowdown

Abstract: Cetaceans (dolphins and whales) have undergone a radical transformation from the original mammalian bodyplan. In addition, some cetaceans have evolved large brains and complex cognitive capacities. We compared approximately 10 000 protein-coding genes culled from the bottlenose dolphin genome with nine other genomes to reveal molecular correlates of the remarkable phenotypic features of these aquatic mammals. Evolutionary analyses demonstrated that the overall synonymous substitution rate in dolphins has slowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 73 publications
5
83
2
1
Order By: Relevance
“…For example, two brains with similar neurophysiologic characteristics, i.e., a similar number of neurons and neural connectivity, may exhibit substantial differences in the number of computations they are able to perform per unit of time as a result of differences in the metabolic turnover of their brains. This fact is particularly interesting, especially when taking into consideration that bottlenose dolphins (and other cetaceans) have a higher basal metabolic rate than terrestrial mammals of the same size and they consume oxygen at a rate that is greater than that documented for both humans and elephants [65,108,109].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, two brains with similar neurophysiologic characteristics, i.e., a similar number of neurons and neural connectivity, may exhibit substantial differences in the number of computations they are able to perform per unit of time as a result of differences in the metabolic turnover of their brains. This fact is particularly interesting, especially when taking into consideration that bottlenose dolphins (and other cetaceans) have a higher basal metabolic rate than terrestrial mammals of the same size and they consume oxygen at a rate that is greater than that documented for both humans and elephants [65,108,109].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is plausible to hypothesize that a faster synaptic transmission speed is possible in the cerebral cortex of cetaceans compared to terrestrial mammals as their metabolism may have evolved to rely more on anaerobic glucose metabolism, especially during periods of increased energy requirements and/or under oxygen deprived conditions (i.e., diving conditions) [121]. For example, the dolphin lineage showed positive for the inheritance of genes involved in the metabolism of glucose and lipids, as well as faster rates of evolution in genes expressed in the mitochondria, both of which indicate an evolution in energy metabolism [65]. Further arguments supporting this perspective come from the work of Williams et al [122] who studied the physiology of the bottlenose dolphin during exercise (i.e., animals either pushing against a load cell or swimming next to a boat).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The apparent elevation in dN/dS is likely to be influenced by the low number of substitutions on short branches. This problem is particularly strong for cetaceans, which have low substitution rates [4]. Second, it is suggested that positive selection is limited to mammalian orders with high EQs.…”
mentioning
confidence: 99%